Biblical commentary on the Psalms ; v. 2 - Delitzsch, Franz Julius, 1813-1890; Bolton, Francis; Wetzstein, J.G. (Edinburgh, Scotland T and T Clark, 1873)
Contents : v. 2 : Psalms 36-83. Includes bibliographical references.
Keywords: Bible. O.T. Psalms XXXVI-LXXXIII -- commentaries